GENETICALLY MODIFIED SOY VERSUS CONVENTIONAL SOY: A COMPARATIVE ANALYSIS OF COSTS AND BENEFITS - Pelaez, Victor; Albergoni, Leide; Guerra, Miguel Pedro (Science & Technology Journals, 2004)
The fast dissemination of the transgenic soybean resistant to herbicides in the USA, in Argentina and clandestinely in Brazil, has been followed by intense debates aiming to compare technical and economic features of this crop vis-à-vis conventional soybean. Despite the fact that more than 60% of worldwide transgenic crops corresponds to soybean production, there are still very few studies capable of providing a conclusive scientific response concerning the techno-economic advantages and disadvantages of such a crop. Likewise, very few is known over economic impacts of conventional soybean commercialization concerning segregation systems. This paper aims to provide a survey of the studies comparing production costs, productivity and profitability between transgenic and conventional soybeans in the USA and Argentina carried out mainly by north-american universities and research institutes. The results indicate that there is not yet fully evidences confirming techno-economic advantages or disadvantages of transgenic soybean in relation to the conventional.